Amin Al-Khouli's Views on The Two Branches of Balaghah: Logical and Literature - Mohammad Izdiyan Muttaqin (Indonesian Journal of Arabic Studies, 2024)
Purpose: This research aimed to analyze Amin Al-Khouli's ideas in distinguishing between the two schools of Balaghah: the literary school and the logical school. Design/Methods/Approach: The research employs a qualitative approach, focusing on several key methods of analysis. Content analysis was conducted, examining both primary and secondary texts. The primary texts include Amin Al-Khouli's writings and publications on Balaghah. The main method of data collection for this research is document analysis, which involves collecting and analyzing a wide range of texts authored by Amin Al-Khouli, including his books "Methods of Renewal" and "The Art of Saying." Findings: The research revealed that Amin Al-Khouli described the literary school of Balaghah as emphasizing the internal meanings of texts, the beauty of style, and literary taste. Key scholars of this school include Abdullah Ibn Al-Mu'taz, Qudamah Ibn Jaafar, and Abdul Qaher Al-Jurjani. In contrast, the logical school focuses on the verbal aspects of rhetoric, such as topic division and term development, with less emphasis on literary taste or internal meanings. Prominent scholars of this school are Abu Ya'qub al-Sakaki, al-Qazwini, and al-Taftazani. Research Implications: This study contributes to the understanding of the development of Balaghah ideas among advanced scholars of the past and highlights Amin Al-Khouli's efforts in bridging the literary and logical schools of Balaghah.